2020
DOI: 10.24843/bulvet.2020.v12.i02.p07
|View full text |Cite
|
Sign up to set email alerts
|

Nilai Hematologi Total Eritrosit dan Kadar Hemoglobin Sapi Bali dengan Pakan Hijauan Organik

Abstract: Hijauan organik telah menjadi pilihan pakan sapi bali di Bali, sehingga perlu diketahui pengaruhnya terhadap rerata total eritrosit dan kadar hemoglobin sapi bali. Penelitian ini menggunakan sepuluh sampel sapi bali betina umur umur 12-18 bulan. Sampel darah diambil melalui vena jugularis menggunakan venoject. Pemeriksaan total eritrosit dan kadar hemoglobin sapi bali diukur dengan alat Veterinary Hematology Analyzer. Hasil penelitian menunjukkan rerata total eritrosit yaitu 6,54x106?l dan rerata kadar hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Hemoglobin is the main component of erythrocytes and functions as the carrier of oxygen and carbon dioxide. The average hemoglobin levels of horned and polled Bali cattle were higher than the hemoglobin levels reported by Siswanto (2011) and Diparayoga et al (2014) but still within the range of reports by Septiarini et al (2020) and Suharti et al (2017) which had hemoglobin levels of 12.53-14.53 g/dl and 10.62±1.21 g/dl, respectively, and in general similar to the result reported by Roland et al (2014).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 80%
“…Hemoglobin is the main component of erythrocytes and functions as the carrier of oxygen and carbon dioxide. The average hemoglobin levels of horned and polled Bali cattle were higher than the hemoglobin levels reported by Siswanto (2011) and Diparayoga et al (2014) but still within the range of reports by Septiarini et al (2020) and Suharti et al (2017) which had hemoglobin levels of 12.53-14.53 g/dl and 10.62±1.21 g/dl, respectively, and in general similar to the result reported by Roland et al (2014).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 80%
“…Hemoglobin levels are also influenced by the adequacy of protein in feed, age, sex, and species (Schalm et al, 1975). Septiarini et al, (2020) study reported a decrease in hemoglobin levels in Bali cattle fed organic forage. It proves that nutrients in feed can also influence hematological levels.…”
Section: Hemoglobin Concentrationmentioning
confidence: 90%
“…Apart from that, the Zn content (0.5 g) in USB can also increase hemoglobin levels. This is by Septiarini et al (2020). Zn supplementation is essential to improve hemoglobin level status in livestock.…”
Section: Hemoglobin (G/dl)mentioning
confidence: 99%